2013
DOI: 10.3109/09638288.2013.808274
|View full text |Cite
|
Sign up to set email alerts
|

Coping and its importance for quality of life in patients with multiple sclerosis

Abstract: Coping is significantly associated with MCS, but not with PCS. Stopping unpleasant emotions and thoughts seems to be the most important type of coping in MS patients. Thus, patients, their caregivers and their physicians should be educated about this type of coping and its positive association with MCS. Implications for Rehabilitation All types of coping are associated positively with mental component of Quality of life. Coping focused on stopping negative emotions and thoughts seems to be very adaptive for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 29 publications
6
37
0
Order By: Relevance
“…In other studies, avoidance has been shown to be an adaptive strategy used for a short time to ward off negative thoughts about future progression of the disease and to avoid depressive reaction (Calandri et al, 2017;Dennison, Yardley, Devereux, & Moss-Morris, 2011;Mikula, Nagyova, & Krokavcova, 2015). According to these authors, when patients have a very little control over their disease, and there is no optimal cure, avoidance can help distract attention from unpleasant emotions and reduce the stress caused by MS (Mikula et al, 2014). However, our results showed no significant relationships with avoidant coping strategies, suggesting more research is needed.…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, avoidance has been shown to be an adaptive strategy used for a short time to ward off negative thoughts about future progression of the disease and to avoid depressive reaction (Calandri et al, 2017;Dennison, Yardley, Devereux, & Moss-Morris, 2011;Mikula, Nagyova, & Krokavcova, 2015). According to these authors, when patients have a very little control over their disease, and there is no optimal cure, avoidance can help distract attention from unpleasant emotions and reduce the stress caused by MS (Mikula et al, 2014). However, our results showed no significant relationships with avoidant coping strategies, suggesting more research is needed.…”
Section: Characteristicmentioning
confidence: 99%
“…Research indicates that people with MS use less adaptive coping strategies over more adaptive problem-focused strategies, due to higher levels of psychological distress and poor quality of life (Goretti, Portaccio, & Zipoli, 2009;Grech et al, 2018). However, recent literature has questioned the maladaptive role of emotional and avoidant coping, indicating that these strategies may be more adaptive than problem-focused coping in the face of uncontrollable stressors (Mikula, Nagyova, & Krokavcova, 2014;Roubinov, Turner, & Williams, 2015). Research on recently diagnosed MS patients revealed that all types of coping strategies should be considered adaptive, as they are associated with a better mental health (Calandri, Graziano, Borghi, & Bonino, 2017).…”
mentioning
confidence: 99%
“…Self-efficacy further influences health behaviors that will be adopted for managing disease outcomes and consequences [4,6]. We finally note that selfefficacy expectations can be manipulated based on targeted sources of efficacy information in the context of research and clinical practice for possibly managing the consequences of MS [8,9]. Such theoretical, research, and clinical relevance supports the importance of studying self-efficacy in the context of MS.…”
Section: Introductionmentioning
confidence: 95%
“…MaTiMS primarily aims to alter coping behavior. To assess this goal, we used the Coping Self Efficacy Scale (CSES), 21 which provides a measure of a person's perceived ability to select the adequate coping strategy for a given challenge and has recently been applied to MS. 22 For assessment of psychological status, quality of life, fatigue, and stress, we used the Hospital Anxiety and Depression Scale (HADS), 23 neuropsychiatric scales of the Hamburg Quality of Life Questionnaire in Multiple Sclerosis (HAQUAMS), 24 the Würzburger Fatigue Inventory for MS (WEIMUS), 25 and the Perceived Stress Scale (PSS). 26 Self-perceived deficits in attention were measured with the Scale to Assess Attention Deficits (SEA).…”
Section: Psychological and Neuropsychological Measuresmentioning
confidence: 99%